2020
DOI: 10.2147/jhc.s259992
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inflammation-Based Prognostic Scores in Patients with Hepatitis B Virus-Related Hepatocellular Carcinoma After Liver Transplantation</p>

Abstract: Background: Inflammation-based prognostic scores including systemic immuneinflammation index (SII), platelet to lymphocyte ratio (PLR) and neutrophil to lymphocyte ratio (NLR) have prognostic value in various cancers. We investigated the prognostic value of SII, PLR and NLR in patients who underwent liver transplantation (LT) for HBV-related hepatocellular carcinoma (HCC). Methods: We retrospectively analyzed the records of 189 patients who underwent LT for HBV-related HCC. The receiver operating characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…SII, a novel prognostic biomarker, can comprehensively reflect the changes in inflammation and peripheral blood counts in the body. In early studies, it was found that increased preoperative SII may be an independent prognostic marker for HCC patients undergoing hepatectomy and liver transplantation and that OS prediction was better than PLR and NLR [21,22]. In addition, a meta-analysis revealed that high preoperative SII was associated with HCC vascular invasion and tumor diameter, which indirectly suggested poor prognosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…SII, a novel prognostic biomarker, can comprehensively reflect the changes in inflammation and peripheral blood counts in the body. In early studies, it was found that increased preoperative SII may be an independent prognostic marker for HCC patients undergoing hepatectomy and liver transplantation and that OS prediction was better than PLR and NLR [21,22]. In addition, a meta-analysis revealed that high preoperative SII was associated with HCC vascular invasion and tumor diameter, which indirectly suggested poor prognosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…These results sometimes can only work when there is a definite recurrence of HCC, so we want to seek some indices which can predict the survival of HCC after LT easily. Recent studies have shown that tumor inflammatory microenvironments can contribute to the risk of proliferation, invasion, and migration of carcinoma [9], suggesting the role of preoperative peripheral blood inflammation markers, such as C-reactive protein levels [10], platelet-to-lymphocyte ratio [11], and neutrophil-to-lymphocyte ratio [12,13] in the postoperative period. In addition, liver inflammation indices such as gamma-glutamyl transferase (GGT), alanine aminotransferase (ALT), aspartate aminotransferase, and lactate dehydrogenase (LDH) levels have been associated with the risk of HCC recurrence after hepatectomy [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory indices in patients with leukopenia and leukocytosis were excluded in the analysis given the likelihood of alterations from an acute infectious or inflammatory process rather than chronic cancer-related effects. In this study, the NLR was calculated by the ratio of the absolute count of neutrophils to lymphocytes, the PLR was calculated by the ratio of the count of platelets to lymphocytes, LMR was calculated by the ratio of the absolute count of lymphocytes to monocytes, ABR was calculated by the ratio of the absolute count of albumin to bilirubin [15] . Moreover, we examined preoperative abdominal imaging and pathology from the resected tumor with recurrence-free survival (RFS) and OS.…”
Section: Methodsmentioning
confidence: 99%